2010
DOI: 10.1038/jhh.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of aldosterone synthase gene (C-344T) and mineralocorticoid receptor (S810L) polymorphisms with gestational hypertension

Abstract: The extent of genetic influence in the aetiology of gestational hypertension has not been completely determined. The aim of this study was to analyse the relationship between aldosterone levels and the -344T/C polymorphism of the aldosterone synthase gene (CYP11B2) and to investigate the frequency of the S810L mutation of mineralocorticoid receptor (MR) in gestational hypertension. One hundred women with pregnancy-induced hypertension and 100 with normal pregnancy were studied to measure serum aldosterone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the context of gestational hypertension, the relationship between aldosterone levels and SNPs of the aldosterone synthase ( CYP11B2 ) gene (−344T/C) and the mineralocorticoid receptor gene (S810L) was investigated in a Mexican population. No differences in genotype distributions or in aldosterone levels were found (Ramírez-Salazar et al, 2011). Similar results were obtained for a Brazilian population (de Vasconcelos et al, 2009).…”
Section: Genetic Studies In Latin-american Populationsmentioning
confidence: 99%
“…In the context of gestational hypertension, the relationship between aldosterone levels and SNPs of the aldosterone synthase ( CYP11B2 ) gene (−344T/C) and the mineralocorticoid receptor gene (S810L) was investigated in a Mexican population. No differences in genotype distributions or in aldosterone levels were found (Ramírez-Salazar et al, 2011). Similar results were obtained for a Brazilian population (de Vasconcelos et al, 2009).…”
Section: Genetic Studies In Latin-american Populationsmentioning
confidence: 99%
“…Although many groups have searched for the presence of the mutation in pregnancy-induced and early-onset hypertension (unpublished results), no other family affected by the disease was described. Surprisingly, a similar and high frequency of the MR 810Leu allele was described in both hypertensive and normotensive pregnant women in a Mexican population, which was not associated to gestational hypertension nor to aldosterone levels at delivery [65]. Although this result suggests that p.Ser810Leu might be common in certain populations, this variant is not described in the Exome variant server (http://evs.gs.washington.edu/EVS/) in the EuropeanAmerican and AfricanAmerican population and there is no indication about the frequency of the variant in Ensembl (http://www.ensembl.org).…”
Section: Activating Mutations Of the Mineralocorticoid Receptormentioning
confidence: 72%
“…The causes of the reduced aldosterone concentration in preeclampsia are not clear. Escher et al [24] found in preeclamptic women a reduced activity of the synthase CYP11B2 which catalyzes aldosterone although the studies on the association of this gene polymorphism with gestational hypertension or preeclampsia remain controversial (see [25] for references). The trophoblast itself is a tissue involved in the transport of numerous ions, such as Na þ through ENaC which are regulated by aldosterone and other factors and hormones as in the epithelia.…”
Section: Resultsmentioning
confidence: 99%